Orchard and riparian habitats enhance ground dwelling beetle diversity in Mediterranean agro-forestry systems - da Silva, Pedro Martins; Aguiar, Carlos a S.; de Faria e Silva, Israel; Serrano, Artur R. M.; Faria e Silva, Israel; Serrano, Artur R. M. (Biodiversity and Conservation, 2011)
The relative contribution of mixed orchard and riparian vegetation patches to local and regional diversity of Mediterranean landscapes dominated by cork-oak woodlands was tested in 2006–2007 using ground, rove and darkling beetles (Coleoptera: Carabidae, Staphylinidae, Tenebrionidae). Mixed orchard and riparian gallery habitats recorded higher values of abundance and species richness for overall beetle species, although most darkling beetle species were associated with the sclerophyllous cork-oak woodlands. Ground and rove beetle community structure changed from the orchard and riparian habitats to samples placed 100 m away into the surrounding cork-oak woodland, i.e., non-cork-oak patches enhanced beta diversity within the landscape mosaic. Analysis of ground beetle traits concerning moisture preferences revealed a higher proportion of hygrophilous species in mixed orchard and riparian gallery habitats while xerophilous species were dominant within the cork-oak woodlands. The results of this study suggested that land-use management promoting the maintenance of habitat heterogeneity enhances biodiversity conservation of important hygrophilous and xerophilous species, and subsequently the sustainable use of Mediterranean agro-forest mosaics.
Keywords: 10; 1007; á land-use intensification á; á moisture traits; article; authorized users; Beta diversity; Coleoptera; coleoptera á beta diversity; contains supplementary material; doi; electronic supplementary material the; Land-use intensiﬁcation; Moisture traits; montado; mosaic á sclerophyllous woodland; online version of this; s10531-010-9987-6; Sclerophyllous woodland; which is available to; ‘‘Montado’’ mosaic